La justicia restaurativa como alternativa para reducir la reincidencia en adolescentes infractores - Coronado Fuentes, Juan Ismael (2025)
The juvenile justice system is focused on juvenile offenders as a group of priority care due to its double vulnerability as it is stated in Constitution. In Ecuador, the legal frame established socio-educational measures, both custodial and non- custodial, designed to foster their rehabilitation and social reintegration. These measures include admonition, community service, and home detention, among others, which are applied according to the severity of the offense. However, the system faces challenges such as recidivism, inadequate infrastructure, and limited family involvement. Restorative justice emerges as an essential approach promoting damage repair and reconciliation between the involved parties to rebuild and strengthen bonds among parties; in this way, to get a better reintegration to society, and consequently, a lower rate of recidivism among adolescents in the future.